2015
DOI: 10.1038/srep18538
|View full text |Cite
|
Sign up to set email alerts
|

High total antioxidant capacity of the porcine seminal plasma (SP-TAC) relates to sperm survival and fertility

Abstract: The study attempted to clarify the role of total antioxidant capacity of seminal plasma (SP-TAC) on boar sperm survival and fertility after artificial insemination (AI). SP-TAC differed (P < 0.001) among boars (n° = 15) and, to a lesser degree, among ejaculates within male (4 ejaculates/boar). SP-TAC also differed (P < 0.001) among ejaculate fractions (43 ejaculates and 3 fractions per ejaculate), of which the sperm-peak portion of the sperm rich ejaculate fraction (SRF) had the highest SP-TAC. SP-TAC was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 31 publications
3
53
0
2
Order By: Relevance
“…In this context, it is well known that the total protein composition differs among boar ejaculate fractions [43]. As in human, the boar ejaculate is expelled in fractions, the SRF and the post-SRF being the two main fractions, with relevant differences in SP-composition [43] including cytokine-contents [44] and antioxidant enzymes [45]. Further research is required to verify possible divergences in the SP-proteome among ejaculate fractions/portions, particularly in the light of the ongoing discussions as to whether to use only the SRF or the entire ejaculate for both AI and sperm technologies, such as cryopreservation and sex-sorting [2].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is well known that the total protein composition differs among boar ejaculate fractions [43]. As in human, the boar ejaculate is expelled in fractions, the SRF and the post-SRF being the two main fractions, with relevant differences in SP-composition [43] including cytokine-contents [44] and antioxidant enzymes [45]. Further research is required to verify possible divergences in the SP-proteome among ejaculate fractions/portions, particularly in the light of the ongoing discussions as to whether to use only the SRF or the entire ejaculate for both AI and sperm technologies, such as cryopreservation and sex-sorting [2].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Barranco et al. () concluded his findings that measurement of seminal TAC ought to be a discriminative tool to prognosis fertility in breeding boars.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is in agreement with findings of others that found the low level of seminal TAC associated with male infertility (Eroglu et al, 2014;Khosravi, Valojerdi, Amanlou, Karimian, & Abolhassani, 2014;Mahfouz, Sharma, Sharma, Sabanegh, & Agarwal, 2009). Recently, Barranco et al (2015) concluded his findings that measurement of seminal TAC ought to be a discriminative tool to prognosis fertility in breeding boars.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins can be used as biomarkers of sperm quality and fertility (Perez‐Patiño et al, ). In addition, the antioxidant enzymes present in the sperm‐rich fraction have a greater total antioxidant capacity (Barranco et al, ), where superoxide dismutase and paraoxonase‐1 are in higher concentrations (Li et al, ). The freezing/thawing of the first two fractions of the ejaculate presents a greater progressive motility and viability, where the antioxidants are involved in cryotolerance, reducing oxidative stress (Li et al, ).…”
Section: Seminal Plasmamentioning
confidence: 99%